TEORI-TEORI PENDIDIKAN KONTEMPORER - Dalilan, Dalilan (Jurnal Bestari, 1993)
There are many improvements and developments in educational teories. In the with the course of the world, there is dialectical process in its affairs. Many philosophers and educators tends to compete to produce "the best" theory of education. This fact begins since a long time ago when Greek Philosophers such as Socrates, Plato and Aristoteles lead the world. This article was translated by Dalilan (student of English Department, Faculity of Teacher Training and Education, University of Muhammadiyah Malang) from George R. Knight, Issues and Alternatives in educational Philosophy, 1982.